Comparing the effect of 8 weeks of concurrent training with and without rest interval on lipid profile and body composition in women with type 2 diabetes - پریسا بنائی; وحید تادیبی; مهرعلی رحیمی (فیزیولوژی ورزش و فعالیت بدنی)
The purpose of this study was to compare the effect of two concurrent training protocols with and without rest between two parts of aerobic and resistance exercise on lipid profile and body composition In women with type 2 diabetes aged 40 to 60 years and BMI > 25. For this purpose, 33 female patients with type II diabetes were randomly divided into 3 groups: 1) concurrent (aerobic-resistance) exercise with 20 min rest in between, 2) concurrent (aerobic- resistance) training with no rest in between, and 3) Control. Training program was performed 3 times a week for 8 weeks. Resistance exercise consisted of 6 exercises, each with 3 sets of 10 repetitions and 90 seconds of rest interval. Aerobic exercise consisted of 30 minutes of aerobic activity. Before and after the intervention, blood sampling and measurements of body composition were performed. Results showed that after 8 weeks of concurrent training levels of cholesterol, triglycerides, low-density lipoprotein, waist-hip ratio, visceral fat mass, and percent of body fat were significantly reduced; and soft lean mass in both training groups increased, significantly. However, there was no significant difference between the changes within the training groups. There were no significant changes for other measured variables and also in the control group. In conclusion we can say that the two of exercise have similar beneficial effects on body composition and lipid profile, however, Due to low blood sugar and fatigue may occur for subjects we offer training concurrent with 20-minute rest interval.